Perancangan Sistem Pelaporan Incident Hack Di Kominfo Lombok Tengah Menggunakan Agile Pendekatan Scrum - Gunawan Efendi; Lalu Mutawalli; Jihadul Akbar (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
The Scrum method is a methodology included in agile software development. Scrum is considered to be able to produce good quality software according to user wishes, can be used in large and small projects, and is easy to adopt changes. The scrum activity stages include product backlog, sprint backlog, daily scrum, sprint review, and sprint retrospective. Roles in Scrum include product owner, scrum master, and development team. Scrum has structured and iterative stages, so that if the product in the first sprint is not sufficient to meet needs, then in the next sprint a system can be developed that is in accordance with user evaluation. The results obtained from Designing a Hack Incident Reporting System at Kominfo Central Lombok Using the Agile Scrum Approach were proven to be able to overcome changes in requirements during the system development phase, producing products that met the wishes of users because they received repeated reviews.